Serosurvey of nonhuman primates in Costa Rica at the human–wildlife interface reveals high exposure to flaviviruses - Chaves, Andrea (2021)
Acknowledgments: We are grateful to all contributors who assisted with sampling endeavors. We would also like to thank the National System of Conservation Areas (SINAC) and the Ministry of Environment and Energy (MINAE) of Costa Rica. We thank the Arbovirus Reference Collection (ARC) from the Centers for Disease Control and Prevention, National Center for Emerging and Zoonotic Infectious Diseases, Division of Vector-Borne Diseases, Arboviral Diseases Branch, Diagnostic and Reference Team, Reference and Reagent Laboratory, and Sanofi Pasteur for supplying the chimeric viruses